(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines the language didactic potential of a poetic text in the context of modern theory and methodology in foreign language teaching. Foreign language teaching has evolved over the years, adapting to new theories and methods to improve language learning outcomes. One area that has received great recognition is the use of poetic texts in foreign language teaching. Poetic texts offer unique linguistic and cultural perspectives that can engage learners and facilitate language acquisition.